Avaliação de um programa de capacitação em saúde bucal para agentes comunitários de saúde - Luz, Luiz Kleber Marconi (2015)
The different methods that use active learning methodology require consistent evaluation process for a new professional profile. Objectives: This Qualitative and quantitative study aimed to evaluate the training and propose an educational model to be developed by the UBSF- Community Health Agents of Itaoca / SP in an Educational Program in Oral Health. Method: Based on the levels of assessment Miller pyramid was conducted the training of Community Health Agents - ACS, 08 professionals. In practical actions used the scale of Turesky Visual Board index that enabled through their scores to obtain statistical data before and after the action taken by the ACS for 413 students representing the students enrolled in the municipal school units and state, in the age group of 6 to 19, also the performance of each ACS, as well as presentation of the variables according to age, gender. It was later applied questionnaire with an interview guide for the ACS, where even answered 10 questions that resulted in a report of action taken by the ACS vision. Results: It was found through the disclosure of Action Plaque and brushing Supervised carried out by the Community Health Agents, which they appropriated the proposed content, regarded as prevention and promotion of oral health, which also provided them professional development with changes in vision and work processes, allowing integration into the oral health team, making the education agents in oral health and consolidating the recovery of health education